527solns3

527solns3 - 642:527 SOLUTIONS: ASSIGNMENT 3 FALL 2007 Some...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 642:527 SOLUTIONS: ASSIGNMENT 3 FALL 2007 Some of these solutions were written by Professor Dan Ocone. 4.5.8 The solutions in the text show how to do these. 9. In the definition (14) of the Gamma function we make the change of variable t = 2 u 2 , dt = 2 u du , which yields (1 / 2) = integraldisplay t 1 / 2 e t/ 2 dt = 2 integraldisplay e u 2 d, . and so, since u is just a dummy integration variable, ((1 / 2)) 2 = bracketleftbigg 2 integraldisplay e u 2 du bracketrightbiggbracketleftbigg 2 integraldisplay e v 2 dv bracketrightbigg = 4 integraldisplay integraldisplay e ( u 2 + v 2 ) du dv. Now we change an integral from Cartesian coordinates ( u, v ) to polar coordinates ( r, ); the integration region u, v 0, which is jusst the first quadrant, becomes 0 / 2, r , and we have change du dv to r dr d . Thus ((1 / 2)) 2 = 4 integraldisplay / 2 integraldisplay e r 2 r dr d = 2 parenleftBig 2 parenrightBig bracketleftBig e r 2 bracketrightBig = . So (1 / 2) = . The change of variables that we did here should really be done somewhat more carefully because the integal is improper, but we will omit these details. 4.6.1 Let y = a n x r + n . Then y = ( r + n ) a n x r + n 1 and y = ( r + n )( r + n 1) x r + n 2 . Plugging these into Bessels equation x 2 y + xy + ( x 2 2 ) y = 0 gives 0 = summationdisplay ( r + n )( r + n 1) x r + n + summationdisplay ( r + n ) a n x r + n summationdisplay 2 a n x r + n + summationdisplay a n x r + n +2 = summationdisplay bracketleftbig ( r + n )( r + n 1) + ( r + n ) 2 bracketrightbig x r + n + summationdisplay a n x r + n +2 Notice that a n x r + n +2 = 2 a n 2 x r + n , and that ( r + n )( r + n 1)+( r + n ) = ( r + n ) 2 . Thus 0 = summationdisplay bracketleftbig ( r + n ) 2 2 bracketrightbig x r + n + summationdisplay 2 a n 2 x r + n = bracketleftbig r 2 2 bracketrightbig a x r + bracketleftbig ( r + 1) 2 2 bracketrightbig a 1 x r +1 + summationdisplay 2 bracketleftbig( ( r + n ) 2 2 ) a n + a n 2 bracketrightbig x r + n ....
View Full Document

Page1 / 5

527solns3 - 642:527 SOLUTIONS: ASSIGNMENT 3 FALL 2007 Some...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online